1994
DOI: 10.1007/bf01971993
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of immunoglobulin isotype levels in acute pneumococcal bacteremia and in convalescence

Abstract: In 48 patients with a history of a pneumococcal bacteremia, serum taken during the acute phase of the infection was analyzed for IgG and IgG subclasses. Once the patients were free of infection, a serum sample was analyzed for IgG, IgG subclasses, IgA and IgM. In an additional 20 patients, it was only possible to analyze serum from the infection-free phase. Seventeen of 48 (35%) patients had reduced levels of total IgG or of one or more of the IgG subclasses during acute disease. Of the 48 patients in whom bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
(13 reference statements)
0
3
2
Order By: Relevance
“…Recurrent or severe bacterial infections, especially with S. pneumoniae, have been reported in patients with selective IgG2 deficiency or combined deficiency of IgG2 and IgG3 or IgG4. 8,9,23,24 In the present study, low IgG2 levels were not associated with the recurrent otitis media in patients with CAEBV, except for case 2. Hammarstrom et al 25 and Lefranc et al 26 have reported that selective IgG2 deficiency has been discovered among healthy blood donors and that recurrent infection is observed in patients with simultaneous deficiency of IgG2 and IgA.…”
Section: Discussioncontrasting
confidence: 45%
“…Recurrent or severe bacterial infections, especially with S. pneumoniae, have been reported in patients with selective IgG2 deficiency or combined deficiency of IgG2 and IgG3 or IgG4. 8,9,23,24 In the present study, low IgG2 levels were not associated with the recurrent otitis media in patients with CAEBV, except for case 2. Hammarstrom et al 25 and Lefranc et al 26 have reported that selective IgG2 deficiency has been discovered among healthy blood donors and that recurrent infection is observed in patients with simultaneous deficiency of IgG2 and IgA.…”
Section: Discussioncontrasting
confidence: 45%
“…We found a high rate of Ig abnormalities, with 45 of the 119 (37.8%) patients having an abnormal Ig and 20 of the 109 adult patients having a low IgG level (18.3%). These proportions, although high, are lower than those reported by Ekdahl et al 11 All but one of these deficiencies occurred in adults, although children were under-represented in our study, probably because of vaccination protection in developed countries. The only deficiency we observed in children was a partial IgA deficiency in a 1-year-old girl with H. influenzae meningitis.…”
Section: Immunoglobulin Deficienciescontrasting
confidence: 85%
“…Herer et al found no variation in Ig levels during community-acquired pneumonia at admission, at recovery, or after discharge, 23 although Ekdahl et al found lower IgG levels during acute infections. 11 Another study performed by Venet et al during septic shock found lower IgG and IgM, but not IgA levels during the first 4 days, with normalization thereafter. 24 In the present study, Ig deficiency was unknown or unexplained in 26 cases, and therefore a second analysis should always be performed in such cases to confirm the deficiency, as the infection may have caused the lower Ig levels.…”
Section: Study Limitationsmentioning
confidence: 93%
See 1 more Smart Citation
“…It contains 60–80 mg/mL of proteins in addition to various small molecules including amino acids, lipids, salts, and sugars (Burtis et al 2001). Normal human serum mainly contains the following proteins: IgG, IgM (Ekdahl et al 1994), IgA, haptoglobulin, albumin (Era et al 1995), transferrin (Burtis et al 2001), α 1 -anti-trypsin, fibrinogen, α 2 -Macroglobulin, and complement C 3 , those account for >95% of total serum proteins (Anderson and Anderson, 2002), many of which are synthesized and secreted, shed, or lost from cells and tissues throughout the body (Schrader and Schulz-Knappe, 2001; Kennedy, 2001). …”
Section: Introductionmentioning
confidence: 99%